Embroideries on Garments from Kurgan 20 of the Noin-Ula Burial Ground - Polosmak, Natalia V. (Anabasis. Studia Classica et Orientalia, 2012)
Kurgan 20 was excavated by the Russian-Mongolian expedition in 2006 in the Xiongnu burial ground called Noin-Ula (Mongolia). It contained fragments of embroidered clothing. The present article deals with miniature representations of warriors and fantastic creatures embroidered in silk by Chinese craftswomen. They must have worked at the shaniuy’s headquarters and have been well-acquainted with western embroideries on wool, judging by the finds from other kurgans in Noin-Ula.